Ecclesiological Theology in the House Church Movement: Literary Study of Church Transformation in the Postmodern Era - Lambertus, Frederich Oscar (Sekolah Tinggi Teologi Injili Indonesia Surabaya, 2024)
This research examines ecclesiology in the context of the house church movement, which emerged as a response to the dynamics of postmodernism. Using the qualitative descriptive content analysis method, this research explores the theological and structural changes that occur in the house church model, as well as the challenges and potential it faces. Postmodernism, which rejects central authority and emphasizes pluralism and individuality, has created conditions favorable to the development of house churches, which are more participatory, decentralized, and community-based. However, this research also highlights the risks facing house churches, including theological fragmentation and a lack of control over orthodoxy. This research finds that despite these challenges, house churches are able to respond to the needs of postmodern society in a flexible and contextually relevant way. Digital technology plays an important role in expanding the reach of house churches, while maintaining community intimacy. Additionally, this research suggests that collaboration between house churches and institutional churches can strengthen overall ecclesiology by combining innovation and stability. The house church is predicted to have the potential to continue to develop in the future, serving as a relevant and significant ecclesiological model for an ever-changing global context.